Smart copolymers of ditriphenylaminedithienothiophene with ethylenedioxythiophene for multicolor energy storage systems. (19th July 2022) - Topal, Sebahat; Karakaya, Ozan; Sezer, Esma; Ustamehmetoglu, Belkis; Ozturk, Turan
Summary: Energy storage materials, having multifunctional properties, are particularly important for the development of intelligent power systems. In this study, conjugated monomers 4′, 4′‐(dithieno[3, 2‐ b :2′, 3′‐ d ]thiophene‐3, 5‐diyl)bis( N, N ‐diphenyl‐[1, 1′‐biphenyl]‐4‐amine) (DTTpTPA, D) and 3, 4‐ethylenedioxythiophene (EDOT, E) were electrocopolymerized on ITO surface in different mole ratios. The copolymer films were investigated in terms of energy storage, electrochromic properties and surface morphology. Inclusion of EDOT units into the polymer chain made a significant impact on the energy storage and electrochromic properties of the resultant copolymers. The P(D1‐1E) film, which was obtained at a mole ratio of n D / n E  = 1/1, showed the best capacitance value of 22 mF cm −2 . All the copolymers displayed a wide range of color change during their redox processes. The best coloration efficiency value of 196 C −1  cm 2 was obtained with P(D10‐1E) film, having multi‐electrochromic property of red, green, gray and blue colors. A symmetric solid‐state energy storage device of P(D1‐1E) exhibited a capacitance of 6.58 mF cm −2 with high energy and high‐power density, which proved that P(D1‐1E) is a good candidate for energy storage applications. Abstract : Electrochemical copolymerization technique was used to obtain the conjugated porous polymer films directly on ITO electrode surface. Multicolor electropolymers showed high areal capacitance of 22 mF cm −2 (P(D1‐1E)) and high color efficiency of 196 C −1 cm 2 (P(D10‐1E)), during their charging and discharging processes.